Microsoft SQL server 2012 step by step - LeBlanc, Patrick; Microsoft Press (Delhi PHI Learning, 2013)
"Teach yourself how to use SQL Server 2012--one step at a time. Ideal for beginning database administrators and developers, this tutorial provides practical, learn-by-doing exercises to help you design and manage databases, develop reports, and employ business intelligence systems"--P. [4] of cover.
includes index
"Microsoft Press"--spine.
Keywords: Database management